ANALISIS PENDAPATAN DAN NILAI TAMBAH KELAPA MENJADI KOPRA DI DESA BOLUBUNG KECAMATAN BULAGI UTARA KABUPATEN BANGGAI KEPULAUAN - Neeke,Made Antara,Alimuddin Laapo, Hasnun (AGROTEKBIS, 2015)
This study aim is to determine the income of farmers in managing the coconuts into the copra and analyzing of added value that can be created to manage the coconut into the copra. This research was conducted in the Bolubung village of North Bulagi Subdistrict of Banggai Islands Regency. This location of research was done by purposive with the consideration that the Bolubung village is one of Village of Oil Production Centers. The timing of the study began in October to November 2014. The analytical tool used is a the income and added Value analysis. The Results showed that the average income whose got a coconut farmer's from the sale of copra of Rp 4,535,757 and added value obtained coconut farm in the village of Bolubung is Rp 955 per kilogram with an output value that is of Rp 1,260 and the value of the input of Rp 305.